Two new species and a review of the inseminating freshwater fish genus Monotocheirodon (Characiformes: Characidae) from Peru and Bolivia - Menezes, Naércio A.; Weitzman, Stanley H.; Quagio-Grassiotto, Irani [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2013)
Two new species of inseminating freshwater fishes of the genus Monotocheirodon, family Characidae, are described from Peru. Males and females of both new species have an external, visually obvious urogenital papilla that was not detected in the females in previous studies, with this longer in males, which use it as an inseminating organ. A third inseminating species from Bolivia, Monotocheirodon pearsoni, unstudied in any detail since its original description in 1924, is redescribed. This latter species lacks an inseminating organ. Monotocheirodon is redescribed, its phylogenetic relationships are briefly discussed and it is suggested that it is possibly related to the stevardiin genera Ceratobranchia, Othonocheirodus, and Odontostoechus.
Keywords: Inseminating characid fishes; New species and relationships of Monotocheirodon